Exploring the Essential Factors on Digital Islamic Banking Adoption in Indonesia: A Literature Review - Elmira Siska (Jurnal Ilmiah Ekonomi Islam, 2022)
The Islamic banking sector is going to change as a result of shifting customer behavior, rising expectations, the adoption of new technology, and the digitization of business and society in general. Islamic banking must become digitally savvy to survive in this new era of technology. Successful digital banking adoption affects by some factors. The purpose of this research is to identify the key success factor of digital banking adoption on Islamic banking in Indonesia. This study employed a qualitative research design through library research techniques. The author reviewed and analyzed various published publications using a systematic literature review (SLR) approach. The findings of the study highlight that there are three key factors that affect digital banking adoption in Islamic banking. First demographic factors include gender, age, income, and education. The second is psychological factors which include security and trust. Third is technological factors which include relative advantage, compatibility, complexity, perceived risk, and perceived cost.